Post-authorisation safety studies of medicinal products in the system of pharmacovigilance - Rabiega-Przyłęcka, Agnieszka (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The aim of the article is to present the legal conditions of one of the elements of the pharmacovigilance system (pharmacotherapy safety) – post-authorisation safety studies of medicinal products. The analysis embraced requirements and principles of conducting safety tests of medicinal products after the authorisation for admitting them to trading in the light of, in particular, the Pharmaceutical Law of 6 September 2001.